DETERMINATION OF KEY PERFORMANCE INDICATOR WITH BALANCED SCORECARD APPROACH IN PUBLIC SECTOR - Hidayat, Suryo; Maarif, M. Syamsul; Najib, Mukhamad (Universitas Brawijaya, Indonesia, 2017)
Performance measurement in the Secretariat of the Ministry of Administrative Reform and Bureaucratic Reform (PANRB) were not comprehensive and thorough yet, so it is necessary to design a new performance measurement by performance indicators. The approach used is balanced scorecard (BSC). This research was conducted in July-August 2016 using primary and secondary data sources. A number of 53 high officials of the Secretariat of the Ministry of PANRB of echelons I, II, III, and IV were included as the study sample. Data were analyzed with descriptive analysis, crosstab, Chi-square, Eckenrode, and Importance Performance Analysis (IPA). The results showed that a major priority for the BSC was the customer's perspective (10 sub perspectives), followed by internal business (20 sub-perspectives), finance (10 sub-perspectives), learning and growth (20 sub-perspectives). Four perspectives of BSC showed its position on the quadrant of IPA showed at â€˜keep up the good work',˜concentrate here'˜possible overkill, and low priority'. In general, the three priority indicators on each perspective shows good performance with a high level of importance. Nevertheless, there are indicators that still having low performance despite its high level of importance, and vice versa.